AVALIAÇÃO AMBIENTAL CORRELACIONADA AO APROVEITAMENTO TURÍSTICO DO CAJUEIRO DE PIRANGI/RN: MEDIDAS DE CONTROLE E CONTINGÊNCIA - Jeronimo, Carlos Enrique; Gomes, Ilma (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611705753 In Rio Grande do Norte, one of the hallmarks of this natural heritage is the cashew Pirangi, being amajor tourist destination in the state, is visited annually by people throughout the world who areattracted by the title of "World's Largest Cashew Tree." However, the cashew tree canopy hasbeen designed so prominent in the directions east/west, with branches spread over the asphalt,this behavior is explained by the position of the sun (east and west). However annual growthoccurs in all directions favoring impacts surrounding communities. As a way of supportingelements for discussion and technical aspects of preservation of cashew Pirangi-RN, this workdeveloped a technical survey of the main alternatives to redress the impacts of uncontrolledgrowth strong element of tourism in the region, seeking to maintain activity in the region. As well,we evaluate the main routes to preserve the cashew tree, showing aspects of pruning as one ofthe key points of how to behave with the same growth, without damaging the environment andmitigating the impacts of tourist activities in the region. The main points relate to the work thatpruning is the most appropriate method to contain the uncontrolled growth of the species and maintain this powerful element active region's tourism and that interventions must be wellplanned, especially with the choice of the appropriate periods for mitigate adverse effects oncashew.